The effects of an altered photoperiod upon the migratory orientation in the White-throated Sparrow (Zonoirichia albicollis) - (:unkn) unknown (My University, 1977)
A variety of cues are available that a nocturnal migratory bird might use to orient during its journey. Perhaps the best established is their use of the information available in the celestial sky. But how much information do they gain? Experiments have shown that the apparent nightly movement of the stars caused by the earth's rotation aids in providing the bird a north-south axis or compass information (Emlen, 1967b; Gauthreaux, 1969). In addition, certain constellations in the northern circumpolar region are crucial for this axis determination (Emlen, 1967b). The celestial sky also changes in a regular manner with the seasons. Although the configuration of the constellations remains the same,' their location appears to change throughout the year due to the earth's revolution around the sun. Does this seasonal shift contribute to the major reversals of direction taken each year by migratory birds?
Keywords: photoperiod; migration; white-throated sparrow; Zonotrichia albicollis